PENGARUH PENGALAMAN MEMBELI PRODUK FASHION TERHADAP NIAT MEMBELI KEMBALI MELALUI KEPUASAN DAN KEPERCAYAAN PELANGGAN - Suandana, Ni Putu Widantari; Rahyuda, Ketut; Yasa, Ni Nyoman Kerti (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 10 Nomor 1 Tahun 2016, 2016)
repurchase intention through customer satisfaction and trust. Data obtained through questionnaires to 100 respondents through purposive sampling for Internet users in Denpasar who have ever bought fashion products through online at least twice in six months. The analysis technique used in this study is the Partial Least Square and for intervening variables using Sobel test and effect size. The result of this research shows that online fashion buying experience significantly and positively influence the online repurchase intention. The customer satisfaction and trust also significantly and positively influence online repurchase intention. The customer satisfaction also influences their trust positively and significantly. The customer satisfaction and trust emerges as mediating variable of the influence of online fashion product buying experience on online repurchase intention.
Keywords: purchase experiences, customer satisfaction, trust, repurchase intention.